2006
DOI: 10.3892/ijmm.17.2.363
|View full text |Cite
|
Sign up to set email alerts
|

JDP1 (DNAJC12/Hsp40) expression in breast cancer and its association with estrogen receptor status

Abstract: The members of the DnaJ/Hsp40 proteins are highly conserved through evolution, expressed in several tissues and act as co-chaperone regulating protein folding, transport, translational initiation and gene expression. Recently, using cDNA microarray we identified differences in the expression of the JDP1 (DNAJC12) gene, a member of the DnaJ/Hsp40 family, between ER-positive and ER-negative breast tumours. In this study, using quantitative real-time PCR (qPCR) we evaluated the expression pattern of the JDP1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Currently, we have not reached a consensus on the mechanism of gene down-regulation in TAF-I KD cells. However, it is noted that among the genes up-regulated by TAF-I KD, TPD52L1 , TFAP2C , DNAJC12 and TFF1 genes are reported to be estrogen-responsive (1,4143). The transcription of these genes was increased by estrogen in the estrogen receptor (ER)-positive breast cancer cells, such as MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we have not reached a consensus on the mechanism of gene down-regulation in TAF-I KD cells. However, it is noted that among the genes up-regulated by TAF-I KD, TPD52L1 , TFAP2C , DNAJC12 and TFF1 genes are reported to be estrogen-responsive (1,4143). The transcription of these genes was increased by estrogen in the estrogen receptor (ER)-positive breast cancer cells, such as MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Next we examined the effects of 17ß-estradiol and ICI 182,780 on PHLDA1 mRNA expression in MCF-7 cells, a hormoneresponsive breast cancer cell line. The MCF-7 cell line was acquired from the American Type Culture Collection (USA) and cultured as described previously (15). For the experiments, the cells were maintained in RPMI-1640 modified medium, without phenol red, and supplemented with 5% fetal bovine serum or 5% stripped fetal bovine serum, free of steroids, for 48 h before the treatments.…”
mentioning
confidence: 99%
“…While the specific function of DNAJC12 is unknown, the available data indicate that its abundance is regulated by physiological stimuli. De Bessa et al (2006) previously reported that female sex steroids (estrogens) upregulate DNAJC12 mRNA levels in estrogen-sensitive MCF7 human breast cancer cells. In addition, we recently made the interesting observation that DNAJC12 mRNA is upregulated by the transcription factor androgen-induced bZIP/CREB3L4 (AIbZIP) in human prostate cells ).…”
Section: Introductionmentioning
confidence: 99%